PENGARUH MANAJEMEN LABA, UKURAN PERUSAHAAN, KINERJA PERUSAHAAN, CORPORATE COMPLEXITY, DAN CEO HOLDINGS TERHADAP SKEMA BONUS - Fanani, Zaenal; Mikail, dan Ahmad (Journal of Accounting and Strategic Finance, 2010)
This research was aimed to examine and to obtain empirical evidence on earnings management, firm size, company performance, corporate complexity, CEO holdings toward bonus schemes. Sample of this research were chosen by using purposive sampling of 129 manufacturing business listed in the Indonesia Stock Exchange (BEI), in the year 2007. Results show that company performance have significant effect on bonus schemes, but earnings management, firm size, company performance, corporate complexity and CEO holdings don't have significant effect on bonus schemes. Keywords: Earnings Management, Firm Size, Company Performance, Corporate Complexity, CEO Holdings, Bonus Schemes